Evolving efficacy of managerial capital, contesting managerial practices, and the process of strategic renewal - Pratap, Sankalp; Saha, Biswatosh (Strategic Management Journal, 2018)
[Research summary: This article examines the adaptation process of a large manufacturer in the Indian steel industry faced with radical sociopolitical shifts in the external ecosystem. It uses the Bower-Burgelman process model in combination with Bourdieu's praxis theory to explain the emergence of competing managerial initiatives and associated contests in the company's internal ecology of strategy-making in terms of socially acquired dispositions. It illuminates process–practice pathways through which top management's resource allocation supported changes in the efficacy of the different forms of capital of the contesting managerial classes, thereby legitimizing the daily "doings" of the rising class and institutionalizing a (re)defined adaptive rule structure. Managerial summary: How do managers' early influences, including family upbringing and schooling, bear upon organization's renewal strategy? Our study finds that during discontinuities imposed by socioeconomic upheavals, when organizational performance flounders, managerial initiatives are driven by deepest dispositions derived from early age socialization. Competing managerial fractions jostle to impose practices favorable to their longstanding preferences by putting their weight behind preferred product-market choices and seeking appropriate changes in the ineffective internal rule structure. Administration's challenge lies in leveraging internal contests to iteratively allocate resources in search of winning dispositions and configurations aligned with evolving social relations in the external environment. Internal availability of managerial groups from diverse social origins is crucial for the administration to reclaim organizational advantage by arbitrating between contesting practices and practitioner fortunes.]